The Correlation of Length of Using IUD and Hemoglobin Levels in IUD Acceptors - Galuh Ajeng Ayu Kinanti; Arika Indah Setyarini; Ririn Indriani (STIKes Patria Husada Blitar, 2023)
IUD is a device inserted into the uterus that is very effective and long term. Behind the success of IUD, there is a side effect that often occurs, called menorrhagia. Prolonged menorrhagia will cause a decrease in hemoglobin levels which can lead to anemia. The purpose of this study was to determine the correlation between the length of using intrauterine devices and hemoglobin levels in IUD acceptors at Keniten Village, Mojo District, Kediri Regency. This type of research was a quantitative research by using observational design with Cross-Sectional approach. The population in this study were 53 IUD acceptors by using Probability Sampling called Simple Random Sampling, which obtained 35 respondents. This research used questionnaires as the instrument to obtain general data, birth control participant card, and hemoglobin measurement tool with Easy Touch brand. There was a significant correlation between the length of using IUD and hemoglobin levels in IUD acceptors. So it can be concluded that the use of IUD for more than 5 years can potentially lead to a greater reduction of hemoglobin levels in IUD acceptors. This can be used as a source of reference for prospective IUD acceptors about side effects, prevention, and treatment if they experience side effects from IUDs.